IMPROVING STUDENTS READING SKILL THROUGH QUIZIZZ APPLICATION OF THE TENTH GRADE STUDENTS OF SMA NEGERI 1 PANGKEP - Magfiratul Jannah Rasyid; Andi Tenri Ampa; Andi Asri Jumiaty (FKIP Unismuh Makassar, 2021)
The Research aimed at investigating the use of Quizizz Application in Improving students’ reading skill. A Pre Experimental design was employed only one clasess of the tenth graders at one school in Kab.Pangkep selected with total sampling as sampel. The data were obtained through a pre-test and a post-test. The Reading Comprehension was convering identify Literal Comprehension (The Main Ideas) and Interpretative Comprehension (Understanding Vocabulary). The compulation shows that the used Quizizz Application was improving the students’ reading comprehension skill, students’ reading comprehension skill using the Quizizz Application indicate better learning results than before the Quizizz Application was applied. The result of pre-test and post-test, the result of t-test value of level significant (p) = 0,05 with degree of freedom in Literal (Main Idea) (df) = 21; in Interpretative (understanding Vocabulary)(df) = 21. Indicated t-table value is 1.720 and t-table Literal (Main Idea) is 6.868; in Interpretative (Undestanding Vocabulary) 4500. After the calculating the value t-test analysis, the is it compared with t-table value. As the result, the researcher notices that the value of t-test is higher than the t-table. It means that null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted. Because there is difference substantial mean score of the test that have provided by researcher using Quizizz Application in Reading Class.